Regulatory problems and developmental psychopathology within the first 2 years of living—a nested in cohort population-based study - Ammitzbøll, Janni; Olsen, Anne Lise; Landorph, Susanne; Ritz, Christian; Skovgaard, Anne Mette (Frontiers in Child and Adolescent Psychiatry, 2024)
Background Infancy regulatory problems (RP) of sleep, feeding and eating, and excessive crying are thought to play a key role in the development of psychopathology in childhood, but knowledge of the early trajectories is limited. Objective To explore RP at ages 8–11 months and the associations with mental health problems at 1½ years, and assess the influences of maternal mental health problems and relationship problems. Methods RP was explored in a nested in-cohort sample (N = 416) drawn from a community-based cohort (N = 2,973). Cohort children were examined by community health nurses, using a mental health screening, which included seven items of RP. Follow-up at 1½ years included diagnostic assessment according to the International Classification of Diseases, ICD-10, and the Diagnostic Classification of Mental Health and Developmental Disorders in Infancy and Early Childhood: Revised edition, DC:0-3R. Data analyses included logistic regression models and analyses of the mediation effect of maternal mental health and relationship problems. Results RP of sleep were associated with a 2-fold increased risk of child mental disorder specifically sleep disorders, adjusted odds ratio (OR) 9.3 [95% confidence interval (CI): 2.0–42.9], disorders of behavior and emotions, adjusted OR 2.9 (95% CI: 1.0–8.4), and DC:0-3R regulatory disorders, adjusted OR 2.7 (95% CI: 1.0–7.5). Children with RP of feeding and eating showed an increased risk of overall mental disorder, adjusted OR 1.4 (95% CI: 0.7–2.4), and specifically, feeding and eating disorders, adjusted OR 6.0 (95% CI: 1.6–21.7), disorders of behavior and emotions, adjusted OR 2.2 (95% CI: 0.9–5.8), as well as DC:0-3R regulatory disorders, adjusted OR 1.6 (1.0–7.5). RP of emotional regulation were associated with increased risk of any mental disorder, adjusted OR 1.5 (1.0–2.4), and specifically behavioral and emotional disorders, adjusted OR 2.2 (95% CI: 0.9–5.9) and DC:0-3R relationship disorders, adjusted OR 1.8 (95% CI: 0.9–3.8). The mediation effect of maternal mental health problems and relationship problems ranged between 0% and 48%. Conclusion RP at ages 8–11 months is associated with increased risk of ICD-10 and DC:0-3R disorders at 1½ years. Study findings highlight a group of vulnerable infants in need of preventive intervention to break the early trajectories of psychopathology.